Defining falciparum-malaria-attributable severe febrile illness in moderate-to-high transmission settings on the basis of plasma PfHRP2 concentration. - Hendriksen, I; White, L; Veenemans, J; Mtove, G; Woodrow, C; Amos, B; Saiwaew, S; Gesase, S; Nadjm, B; Silamut, K; Joseph, S; Chotivanich, K; et al. (2013)
BACKGROUND: In malaria-endemic settings, asymptomatic parasitemia complicates the diagnosis of malaria. Histidine-rich protein 2 (HRP2) is produced by Plasmodium falciparum, and its plasma concentration reflects the total body parasite burden. We aimed to define the malaria-attributable fraction of severe febrile illness, using the distributions of plasma P. falciparum HRP2 (PfHRP2) concentrations from parasitemic children with different clinical presentations. METHODS: Plasma samples were collected from and peripheral blood slides prepared for 1435 children aged 6-60 months in communities and a nearby hospital in northeastern Tanzania. The study population included children with severe or uncomplicated malaria, asymptomatic carriers, and healthy control subjects who had negative results of rapid diagnostic tests. The distributions of plasma PfHRP2 concentrations among the different groups were used to model severe malaria-attributable disease. RESULTS: The plasma PfHRP2 concentration showed a close correlation with the severity of infection. PfHRP2 concentrations of >1000 ng/mL denoted a malaria-attributable fraction of severe disease of 99% (95% credible interval [CI], 96%-100%), with a sensitivity of 74% (95% CI, 72%-77%), whereas a concentration of <200 ng/mL denoted severe febrile illness of an alternative diagnosis in >10% (95% CI, 3%-27%) of patients. Bacteremia was more common among patients in the lowest and highest PfHRP2 concentration quintiles. CONCLUSIONS: The plasma PfHRP2 concentration defines malaria-attributable disease and distinguishes severe malaria from coincidental parasitemia in African children in a moderate-to-high transmission setting.